Designing a Child-Centric Android Mathematics Application: A Technological Approach to Early Childhood Cognitive Development - Juliana; Siti Khotijah; Dewi Driyani (Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
Purpose: This study aims to develop a specialized Android-based mathematics learning application to address specific cognitive barriers in grasping fundamental number concepts and basic arithmetic among preschool children at TPQ Al Falah, Depok. Design/methodology/approach: Adopting the Waterfall development model—comprising requirement analysis, system design, coding, and rigorous testing—the study engaged pupils aged 4–6. Research instruments involved qualitative observations, semi-structured interviews, and black-box testing focusing on interactive quiz functionalities to evaluate pedagogical efficacy. Findings: Results indicate that the application effectively facilitates the mastery of numbers 1–10 and basic arithmetic operations. The strategic integration of synchronized audio-visual stimulation and gamification elements significantly enhanced student attention spans and intrinsic learning motivation. Practical implications: The application serves as a robust autonomous tool for educators and parents, facilitating a seamless transition from conventional instructional methods to interactive digital pedagogies. Originality/value: This study contributes to TPACK literature by uniquely synthesizing reversible reasoning and the